2017
DOI: 10.3349/ymj.2017.58.4.689
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption, Aldehyde Dehydrogenase 2 Gene Polymorphisms, and Cardiovascular Health in Korea

Abstract: Alcohol consumption is a serious health issue in Korea in terms of the amount consumed and the behavior related to its consumption. Aldehyde dehydrogenase 2 (ALDH2) is a key enzyme in alcohol metabolism that degrades acetaldehyde to nontoxic acetic acid. The enzyme is coded by the ALDH2 gene, which is commonly polymorphic in East Asian populations. A point mutation in the ALDH2 gene (the rs671 allele) yields an inactive form of ALDH2 that causes acetaldehyde accumulation in the body after alcohol consumption, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 62 publications
1
26
0
Order By: Relevance
“…enzymes, microsomal proteins, and microtubules) and forming adducts with DNA, which ultimately results in impaired target-organ function 21,22 , ALDH2′s acetaldehyde-removal activity has attracted clinical interest. The genetic diversity of ALDH2, on chromosome 12, is well established elsewhere 2,17,[23][24][25] . The G-to-A missense mutation in exon 12, where glutamate at position 504 is replaced by lysine (Glu504Lys), is one of the representative SNPs (rs671) in ALDH2.…”
Section: Discussionmentioning
confidence: 99%
“…enzymes, microsomal proteins, and microtubules) and forming adducts with DNA, which ultimately results in impaired target-organ function 21,22 , ALDH2′s acetaldehyde-removal activity has attracted clinical interest. The genetic diversity of ALDH2, on chromosome 12, is well established elsewhere 2,17,[23][24][25] . The G-to-A missense mutation in exon 12, where glutamate at position 504 is replaced by lysine (Glu504Lys), is one of the representative SNPs (rs671) in ALDH2.…”
Section: Discussionmentioning
confidence: 99%
“… 3 In persons of East Asian ancestry, genetic variants that lead to slower metabolism of alcohol and its metabolite acetaldehyde are much more common than in persons of European ancestry. 4 Thus, the impact of alcohol consumption on the development of type 2 diabetes is likely to depend on patterns of alcohol consumption, sex, and ethnicity. 5 …”
mentioning
confidence: 99%
“… 2 The higher prevalence of variants in alcohol metabolizing genes that can lead to higher circulating concentrations of alcohol and acetaldehyde for the same level of alcohol intake may increase diabetes risk at a lower level of consumption in East Asian populations. 4 Interestingly, a Mendelian randomization study in a Korean population also suggested that moderate alcohol consumption increases fasting blood glucose concentrations in men. 4 This study used ALDH gene variants as an instrumental variable reflecting alcohol consumption.…”
mentioning
confidence: 99%
See 2 more Smart Citations